Changes of Metabolomic Profile in Helianthus annuus under Exposure to Chromium(VI) Studied by capHPLC-ESI-QTOF-MS and MS/MS - Alan Alexander Gonzalez Ibarra; Kazimierz Wrobel; Eunice Yanez Barrientos; Alma Rosa Corrales Escobosa; J. Felix Gutierrez Corona; Israel Enciso Donis; Katarzyna Wrobel (Journal of Analytical Methods in Chemistry)
The application of capHPLC-ESI-QTOF-MS and MS/MS to study the impact of Cr(VI) on metabolites profile in Helianthus annuus is reported. Germinated seeds were grown hydroponically in the presence of Cr(VI) (25 mgCr/L) and root extracts of the exposed and control plants were analyzed by untargeted metabolomic approach. The main goal was to detect which metabolite groups were mostly affected by Cr(VI) stress; two data analysis tools (ProfileAnalysis, Bruker, and online XCMS) were used under criteria of intensity threshold 5 · 104 cps, fold change ≥ 5, and p≤0.01, yielding precursor ions. Molecular formulas were assigned based on data processing with two computational tools (SIRIUS and MS-Finder); annotation of candidate structures was performed by database search using CSI:FingerID and MS-Finder. Even though ultimate identification has not been achieved, it was demonstrated that secondary metabolism became activated under Cr(VI) stress. Among 42 candidate compounds returned from database search for seven molecular formulas, ten structures corresponded to isocoumarin derivatives and eleven were sesquiterpenes or sesquiterpene lactones; three benzofurans and four glycoside or pyrane derivatives of phenolic compounds were also suggested. To gain further insight on the effect of Cr(VI) in sunflower, isocoumarins and sesquiterpenes were selected as the target compounds for future study.